2018
DOI: 10.1038/nm0418-525c
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: Positively selected enhancer elements endow osteosarcoma cells with metastatic competence

Abstract: In the version of this article initially published, the numbers on the y-axis of Figure 2b were incorrect by a power of 10, and the numbers in the text describing the frequency of MSI-H tumors were also incorrect. The original text read: "Still lower, but detectable, frequencies of MSI-H were observed in 12 other cancer types; collectively, one or more individual MSI-H tumors were identified in 16 of the 18 cancer types examined".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…TF expression is also up to 1000-fold greater in metastatic cells than in non-metastatic cells [163]. An unbiased shRNA screen showed that TF is one of the most powerful drivers of metastasis in osteosarcoma [164]. Such correlative findings have been verified by functional studies in vivo [23,163,165].…”
Section: Invasion and Metastasismentioning
confidence: 86%
“…TF expression is also up to 1000-fold greater in metastatic cells than in non-metastatic cells [163]. An unbiased shRNA screen showed that TF is one of the most powerful drivers of metastasis in osteosarcoma [164]. Such correlative findings have been verified by functional studies in vivo [23,163,165].…”
Section: Invasion and Metastasismentioning
confidence: 86%
“…Osteosarcoma (OS), the most common and aggressive type of primary malignant bone tumor, arises most often in children and adolescents 1,2 . It is derived from interstitial tissue and is characterized by heterogeneity, rapid progression, and a high risk of metastasis, primarily to the lungs 3 . Nevertheless, the underlying molecular mechanisms of OS pathogenesis remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 It is derived from interstitial tissue and is characterized by heterogeneity, rapid progression, and a high risk of metastasis, primarily to the lungs. 3 Nevertheless, the underlying molecular mechanisms of OS pathogenesis remain elusive. Hence, it is imperative to investigate the underlying mechanism and develop novel effective targets for the treatment of OS.…”
Section: Introductionmentioning
confidence: 99%